(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The spices are not utilized simply to upgrade flavors to detonate on the taste buds yet assume a vital part in the improvement of the novel. They loan a magical quality and are a methods through which magic realism is utilized as a part of the novel. Divakaruni’s most noteworthy resource is her style since she is offered with a natural feeling of mixing reality and creative energy, the past and the present, fantasy and beliefs. In this thesis We have discussed Magic Realism, Mistress of Species, the Mirror of Fire and Dreaming, Conch of Bearer and Elements of Magic and Power of her novels.